A new strategy of social policy in latin america as an alternative to neoliberalism: the case of the bolivarian missions in venezuela (2009)
The following document has the purpose to present different conceptions and constituting elements of the social policy developed in Latin America, in particular in Venezuela during the past century. Thus, some key features are offered to outline a new paradigm of social policy relevant for the present historic-cultural, politic-institutional and socio-economic conditions of this country. This new paradigm would be in a “construction process” and its theoretical-methodological framework would basically feed from the formulation and running of the current Bolivarian Missions, driven by the revolutionary project frame under which the Venezuelans have been living since the beginning of the XXI century.